Cobalt/nitrogen co-carved carbon nanorod for efficient Fenton-like reaction: Degradation efficacy, reaction mechanism and singlet oxygen generation. (20th February 2023) - Li, Meng; Zheng, Ke; Jin, Yu-Ting; Zhang, Zhao-Xin; Cheng, Ji-Liang; Huang, Long-Wei; Mo, Ce-Hui; Zhou, Shao-Qi
Highlights: A CoNC Fenton-like catalyst can efficiently degrade organic pollutants. It is confirmed that 1 O2 is the dominant active species for degrading organics. A CoN2 C2 ligands structure has the best catalytic activity for peroxymonosulfate activation. The generation pathway of 1 O2 is clearly clarified via DFT calculations. Electrons can be easily transferred from the organics to peroxymonosulfate. Abstract: The Fenton-like process shows promising potential to generate reactive oxygen species for the remediation of increasingly environmental pollutants. However, the slow development of high-activity catalysts with strong stability and low leaching of metal ions has greatly inhibited scale-up application of this technology. Here, cobalt (Co)/nitrogen (N) atom co-curved carbon nanorod (CoNC) containing highly uniform CoN x active sites is developed as a Fenton-like catalyst for the effective catalytic oxidation of various organics via peroxymonosulfate (PMS) activation with high stability. As confirmed by the experimental results, singlet oxygen ( 1 O2 ) is the dominant active species for the degradation of the organics, with a proportion of 100%. Furthermore, density functional theory calculations indicate that CoN2 C2 is the most effective ligand structure with more negative adsorption energy for PMS and the shortest length Co–O bond, while the most reasonable generation pathway for 1 O2 was CoN2 C2 –PMS → CoN2 C2 –OH* → 2O* → 1 O2 . Further studies demonstrate that the electron can be transferred from the highest occupied molecular orbitals of the organics to the lowest unoccupied molecular orbitals of the PMS via CoN2 C2 action. In addition, the CoNC presents strong resistance to inorganic ions and natural organic matter in the Fenton-like catalysis process. The presence of CoN2 C2 active centre can significantly shorten the migration distance of the 1 O2 generated from PMS activation, which further enhances the Fenton-like catalytic activity in terms of mineralising various organic contaminants with high efficiency over a wide pH range.